DISEMINASI PENGOLAHAN SEDERHANA LIMBAH IKAN SEBAGAI DEDAK - Bidayani, Endang; Nugraha, Agung; Priyambada, Agung (Jurnal Pengabdian Perikanan Indonesia, 2022)
Waste from processing salted fish in Batu Be Lubang Village, Pangkalan Baru District, Central Bangka Regency, can be dried into fish bran as raw material for aquaculture fish feed and other animal feed. The bran has economic value, and can be sold for IDR 4,000/kg. The purpose of Community Service (PkM) activities is to help traditional fishermen get a side business from processing fish waste into fish bran/flour with high economic value. The implementation of PkM is participatory or involves the community in the PkM stage which is focused on two areas, namely socialization and implementation of activities. The stages of processing fish waste as bran include: Boiling fish, taking fish stew waste sediment, drying and winnowing.